Comparison of acoustic and elastic full‐waveform inversion of 2D towed‐streamer data in the presence of salt. (30th December 2018) - Thiel, Niklas; Hertweck, Thomas; Bohlen, Thomas
ABSTRACT: Over the last years, full‐waveform inversion has become an important tool in the list of processing and imaging technologies available to the industry. For marine towed‐streamer data, full‐waveform inversion is typically applied using an acoustic approximation because S‐waves do not propagate in water and elastic effects in recorded data are generally assumed to be small. We compare acoustic and elastic modelling and full‐waveform inversion for a field data set acquired offshore Angola over sediments containing a salt body with significant topology. Forward modelling tests reveal that such geological structures lead to significant mode conversions at interfaces and, consequently, to significant relative amplitude differences when elastically and acoustically modelled traces are compared. Using an acoustic approach for modelling in full‐waveform inversion therefore leads to problems matching the synthetic data with the field data, even for recorded pressure data and with trace normalization applied. Full‐waveform inversion is unable to find consistent model updates. Applying elastic full‐waveform inversion leads to more consistent and reliable model updates with less artefacts, at the expense of additional computation cost. Although two‐dimensional marine towed‐streamer data are least favourable for the application of full‐waveform inversion compared to three‐dimensional data or ocean‐bottom data, it is recommended to check on the existence of elastic effects before deciding on the final processing and imaging approach.